Symbolic use of wind-catchers in Iran - Sani, Rafooneh Mokhtarshahi; Shotorbani, Payam Mahasti (My University, 2013)
In recent decades, Iranian vernacular architecture has defined the local architectural identity by demonstrating distinctivecharacteristics. Defining such a critical role for vernacular studies has led to different approaches in the design ofthe contemporary architecture of Iran. The first approach of integrating vernacular and contemporary designs hasfocused on local people, their needs, local construction, and building materials. The revival of vernacular architecturaldesign and building elements has been at the forefront of this approach in Iran. However, recent use in Iran has concentratedon the symbolic/abstract reuse of vernacular building forms. Vernacular architecture is known to merely providefor the functional requirements of buildings, and not for aesthetic purposes. Conversely, in the second approach,vernacular building elements are considered to be symbols of local identity. This paper will argue that although the symbolicreuse of vernacular features may not uphold the functional expectations of the vernacular form, this reuse is usefulin reviving architectural identity. In addition, underscoring such a different role for vernacular building features incontemporary architecture might help to expand the realm of vernacular studies. Thus, the purpose of this paper is toprovide an overview of the conversion of vernacular architecture in Iran by focusing on the instance of wind-catchers.Wind-catchers typically were used in residential buildings and are considered potent symbols of climate adaptation. Incontemporary architecture, however, a form of wind-catcher has been used as a symbol for local architectural identity.Through this transformation, the essential nature of the wind-catcher has found new life in the contemporary architectureof Iran.
Keywords: Identity; Iran; Symbol; Vernacular; Wind-catchers